Perturbing phytoplankton: response and isotopic fractionation with changing carbonate chemistry in two coccolithophore species - Rickaby, R; Henderiks, J; Young, J (2010)
All species of coccolithophore appear to respond to perturbations of carbonate chemistry in a different way. Here, we show that the degree of malformation, growth rate and stable isotopic composition of organic matter and carbonate produced by two contrasting species of coccolithophore (Gephyrocapsa oceanica and Coccolithus pelagicus ssp. braarudii) are indicative of differences between their photosynthetic and calcification response to changing DIC levels (ranging from ∼1100 to ∼7800 μmol kg-1) at constant pH (8.13 ± 0.02). Gephyrocapsa oceanica thrived under all conditions of DIC, showing evidence of increased growth rates at higher DIC, but C. braarudii was detrimentally affected at high DIC showing signs of malformation, and decreased growth rates. The carbon isotopic fractionation into organic matter and the coccoliths suggests that C. braarudii utilises a common internal pool of carbon for calcification and photosynthesis but G. oceanica relies on independent supplies for each process. All coccolithophores appear to utilize bicarbonate as their ultimate source of carbon for calcification resulting in the release of a proton. But, we suggest that this proton can be harnessed to enhance the supply of CO2(aq) for photosynthesis either from a large internal HCO 3- pool which acts as a pH buffer (C. braarudii), or pumped externally to aid the diffusive supply of CO2 across the membrane from the abundant HCO3- (G. oceanica), likely mediated by an internal and external carbonic anhydrase respectively. Our simplified hypothetical spectrum of physiologies may provide a context to understand different species response to changing pH and DIC, the species-specific εp and calcite "vital effects", as well as accounting for geological trends in coccolithophore cell size. © Author(s) 2010.